Partisipasi Masyarakat Dalam Pengelolaan Sampah di Kabupaten Badung - Yuliastuti, Ida Ayu Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; Volume.02.N0.06.Tahun 2013, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Badung tourism as one of the problems faced with the increasing amount of waste is due to the addition of the population and increased human activity . Waste generation should be managed with the help of community participation . Community participation in waste management is dependent upon the understanding , and the willingness of the public revenues to improve the quality of the environment . The purpose of this study was to determine the effect of the understanding , the will , and income simultaneously and partially on public participation in waste management in Badung regency . This study uses primary data from 94 respondents who constitute the five major sectors of the waste that is served by the transportation of waste and Sanitation Department ( DKP). Sampling using the Proportionate random sampling method . Analysis techniques in this study using multiple linear regression analysis . The results showed that understanding , willingness , and income simultaneously significant effect on community participation in waste management in Badung regency . Partial understanding , willingness , and income and a significant positive effect on community participation in waste management in Badung regency . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:EN-US; mso-fareast-language:EN-US;}
Keywords: community participation, understanding, willingness, income